Luchas por la tierra, contradicciones sociales y sistema político. El caso de las zonas ejidales y comunales en la ciudad de México, 1980-1984 - Calderón Cockburn, Julio (El Colegio de México A.C., 1987)
This paper analyzes the results of a research project which consisted mainly of studying the newspapers of the 1980-1984 period, interviewing leaders of popular quarters and checking all literature available. It aims at describing the most relevant characteristics of the struggles for land, in the ejidal and communal zones of the metropolitan area of Mexico City, between 1980 and 1984.The article first mentions the general context within which these struggles took place (particularity how urban growth occurred at the expense of communal land, specially those lands which had been given to the peasants because of the agrarian reform). The paper then concentrates on analyzing the social contradictions which resulted from the ilegal sales of these lands. The author, after studying the newspapers of this period, discusses the people mobilized during the struggles, their relationship with the aims of the mobilization and the antagonism between these people and their adversaries for each of the cases studied. As a result of this, the author has also been able to inform us about the number and type of struggles which took place in the area and period analyzed he also presents us with a view of the main characteristics of the protagonists and of the motives which lead them to mobilize.The paper ends with an attempt to interpret these struggles; this interpretation is based on a characterization of the Mexican political system which is also briefly presented here. Moreover, the author has taken into account some concepts by social researchers who have theorized on social movements.Finally he concludes that even though the social conflicts analized here have not affected the present system of power in Mexico, important politically biased struggles, which have altered the traditional channels of people participation, have taken place.